An Audit of Pain Management Following Pediatric Day Surgery at British Columbia Children’s Hospital - Serena Shum; Joanne Lim; Trish Page; Elizabeth Lamb; Jennifer Gow; J Mark Ansermino; Gillian Lauder (Pain Research and Management)
A prospective audit of 225 children was conducted to evaluate current pain management strategies both in-hospital and at home following day surgery at British Columbia Children’s Hospital (Vancouver, British Columbia). Anesthetic, postanesthetic care unit and surgical day care unit records were collected to generate in-hospital data. A telephone questionnaire was administered 48 h postdischarge for at home data. Pain reports and scores were significantly higher (P<0.01) at home compared with in-hospital. Children undergoing certain procedures were more likely to experience significant pain. Although good pain control was commonly achieved after surgery, improvements may be possible by increasing the use of multimodal analgesia, providing standardized written discharge instructions and using surgery-specific pediatric analgesia guidelines.